Efficient generation of fast neutrons by magnetized deuterons in an optimized deuterium gas-puff z-pinch; Plasma Physics and Controlled Fusion; Vol. 57, iss. 4 - Klir D.; Shishlov A. V. Aleksandr Viktorovich; Kokshenev V. A. Vladimir Alekseevich; Kubes P.; Labetsky A. Yu. Aleksey Yurjevich; Rezac K.; Cherdizov R. K. Rustam Koshalievich; Cikhardt J. Jakub; Cikhardtova B.; Dudkin G. N. Gennadiy Nikolaevich; Fursov F. I. Fedor Ivanovich; Garapatski A. A. Alexander Alexandrovich; et al. (2015, 2015)
Title screen